Utveckling Ulricehamn - Karlsson, Maria (2006)
The purpose of this thesis is to inquire how a small town can be affected by some planned changes in the physical structure of the town, and how its inhabitants can benefit from those major changes. The town in question is Ulricehamn, and of the four projects considered, two concerns infrastructure. A new railway and a new locality for the major road, today passing through Ulricehamn. The other two projects are run by the local authorities, that is the planning of a modern town park by the lake, and a new public building for cultural purposes. There are no guarantees that any of the four projects will ever be realized, but in the process with this work, they have been considered as already a fact. That has been the starting point to the reasoning about change and development in Ulricehamn. The work aims to be visionary, and there has been no search for absolute answers to the questions asked. Finding out what the present situation in Ulricehamn is like, has been central throughout the process. Ulricehamn is a small town with weaknesses as well as strong sides. It is situated in beautiful surroundings and offers opportunities for recreation and outdoor life. The projects concerning infrastructure are beneficial to the town by giving opportunities for traveling and commuting. With a railroad through the town, the number of people passing through will increase, and all travelers can be seen as presumptive visitors or settlers in Ulricehamn. Therefore it is of importance to consider how to design the area around the railway station. A new park by the lake will finally give the city a well thought-out water front. The park will increase the use of the lakeshore by making it more attractive and more accessible. The railway station will be situated slightly outside the town centre, but will be connected to the centre by one street. With a new railway station, the area around this street might develop into a lively neighbourhood. The fact that this area is adjacent to the new city park makes it even more interesting, it might also be the right place for a new public building and in a long perspective also for new housing. The design of the area in which the four planned projects take place is crucial to how Ulricehamn will meet the future. However, even more important is the people of Ulricehamn. How they look at their city, and what they do in it, will finally shape Ulricehamn and fill the town with meaning and life.